Azaarene dimers - Hahn, Sebastian; Butscher, Julian; An, Qingzhi; Jocic, Angelina; Tverskoy, Olena; Rominger, Frank; Vaynzof, Yana; Bunz, Uwe H. F. (Chemistry - a European journal, 2019)
Binaphthyl-3,3′,4,4′-tetraone was prepared and coupled to different bis(TIPS-ethynyl)-substituted (TIPS=triisopropyl silane) aromatic diamines, resulting in the formation of dimeric benzo-fused azaacenes, centrally connected by a single bond. The two halves of the molecules are highly twisted with respect to each other and showed limited electronic interaction in the ground state because their absorption spectra remained very similar to those of the constituting monomers. The dimers displayed greatly reduced fluorescence when compared to the monomers, suggesting that there is a significant interaction of the two azarene units in the excited state. Preliminary investigations showed that the dimers are attractive for application as acceptors in organic photovoltaic because they significantly outperform their monomeric counterparts.